(untitled) (LEGAL DIALOGICA, 2025)
The aim of this research is to determine the inheritance distribution system based on the responsibility of PPAT for the certification of customary land and analyze what obstacles are faced by PPAT officials. In this study using empirical research methods, the types and sources of data used are primary and secondary data with data collection techniques namely library research and interviews. The results of the study show that the responsibility of PPAT is important in the implementation of customary land certification and provides legal data and complies with applicable laws. Research recommendations on the legal review of the professional responsibility of land deed officials for the certification of customary land, namely incomplete land documents that require a certificate from the village head or village head and witnesses who strengthen the boundaries of the land in determining the object of customary land are not available. Abstrak: Tujuan penelitian ini guna mengetahui tanggung jawab PPAT terhadap persertifikatan tanah milik adat serta menganalisi kendala apa saja yang dihadapi oleh pejabat PPAT. Dalam penelitian ini mempergunakan metode penelitian empiris, jenis dan sumber data yang dipergunakan yaitu data primer dan sekunder dengan teknik pengumpulan data yaitu penelitian pustaka dan wawancara. Hasil penelitian memperlihatkan bahwa tanggung jawab PPAT penting dalam pelaksanaan persertipikatan tanah milik adat dan memberikan data yuridis serta mematuhi undang-undang yang berlaku. Rekomendasi penelitian pada tinjauan yuridis tanggung jawab profesi pejabat pembuat akta tanah atas persertfikatan tanah milik adat yakni surat-surat tanah yang tidak lengkap sehingga memerlukan surat keterangan lurah atau kepala desa dan saksi yang menguatkan batas-batas tanah dalam menentukan obyek tanah milik adat tidak ada.